Green Information Technology in Indonesia– A Systematic Literature Review - Zahra Nurkarima Budiwati Attori; Udisubakti Ciptomulyono; Satria Fadil Persada (IPTEK Journal of Proceedings Series, 2020)
In Indonesia, information and communication technology (ICT) is one of the most crucial economy accelerators, for every 10% increase in the ICT investment, the nation’s GDP grows as much as 1.87%. However, the use of ICT leaves adverse impacts on the environment, particularly carbon emission and toxic waste. This phenomenon has led to the proliferation of the topic of environmental sustainability, one of which is green information technology (GIT). GIT is defined as the utilization of ICT that can directly or indirectly reduce the adverse impact of business processes on the environment. This paper aims to evaluate GIT research to attain a better understanding of the field of GIT in Indonesia through a literature review. Published papers are categorized and a gap analysis is presented to reveal areas that need to be explored more. The results of this study potentially serve as a guide for future studies in GIT, particularly in Indonesia. This research finds that the topic has gained popularity in recent years. There are various research themes under the topic of GIT in Indonesia, with the most explored one being the design and implementation of GIT. The majority of the studies are case-based, limiting the research scope to one particular organization. This leaves broader research objects open to be explored more.